Familicidal hearts the emotional styles of 211 killers - Websdale, Neil. (New York ; Oxford : Oxford University Press, 2010)
Websdale uncovers the stories behind 196 male and 15 female perpetrators of murder, situating their emotional styles on a continuum, from the coercive to the civil reputable. With detailed case studies, Websdale explores the pivotal roles of shame, rage, fear, anxiety, and depression in the lives and crimes of the killers.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Family violence -- Psychological aspects; Homicide -- Psychological aspects; Uxoricide -- Psychological aspects; Infanticide -- Psychological aspects